2021
DOI: 10.3390/electronics10131525
|View full text |Cite
|
Sign up to set email alerts
|

Improving Heterogeneous Network Knowledge Transfer Based on the Principle of Generative Adversarial

Abstract: Deep learning requires a large amount of datasets to train deep neural network models for specific tasks, and thus training of a new model is a very costly task. Research on transfer networks used to reduce training costs will be the next turning point in deep learning research. The use of source task models to help reduce the training costs of the target task models, especially heterogeneous systems, is a problem we are studying. In order to quickly obtain an excellent target task model driven by the source t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Lei et al used source task models to help reduce the training cost of target task models in order to reduce the neural network training cost. They proposed a new migration learning method which linearly transforms the feature mapping of the target region, increases the weights of feature matching, enables knowledge transfer between heterogeneous networks, and adds discriminators based on adversarial principles to speed up feature mapping and learning [10]. Sharipuddin et al addressed the intrusion detection system in heterogeneous networks which is easily affected by objective factors such as devices and network protocols, proposed an identification method combining deep learning, and conducted preliminary experiments on denial-of-service attacks, and the experimental results showed that deep learning can improve the detection accuracy in heterogeneous networks [11].…”
Section: Related Workmentioning
confidence: 99%
“…Lei et al used source task models to help reduce the training cost of target task models in order to reduce the neural network training cost. They proposed a new migration learning method which linearly transforms the feature mapping of the target region, increases the weights of feature matching, enables knowledge transfer between heterogeneous networks, and adds discriminators based on adversarial principles to speed up feature mapping and learning [10]. Sharipuddin et al addressed the intrusion detection system in heterogeneous networks which is easily affected by objective factors such as devices and network protocols, proposed an identification method combining deep learning, and conducted preliminary experiments on denial-of-service attacks, and the experimental results showed that deep learning can improve the detection accuracy in heterogeneous networks [11].…”
Section: Related Workmentioning
confidence: 99%
“…Currently, data is still in the form of isolated islands due to issues such as competitive relationships and trust levels among industries, enterprises, and even individuals. Traditional distributed machine learning [5,6] collects all data for unified training. However, in many applications, data is scattered among mobile edge devices and cannot be shared and transmitted safely and effectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of big data, the field of artificial intelligence is making a splash, [1][2][3][4][5][6][7][8]. Accurate prediction plays a crucial role in our modern life, where the research of prediction methods based on machine learning, especially neural networks, has become increasingly popular, [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%